2015
DOI: 10.1155/2015/582769
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Artery Cement Embolism after a Vertebroplasty

Abstract: Background Context. Vertebroplasty is a minimally invasive procedure most commonly used for the treatment of vertebral compression fractures. Although it is relatively safe, complications have been reported over time. Among those complications, massive cement pulmonary embolism is considered a rare complication. Here we report a case of massive diffuse cement pulmonary embolism following percutaneous vertebroplasty for a vertebral compression fracture. Study Design. Case report. Methods. This is a 70-year-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…The presentation can vary from an incidental radiological finding to a life-threatening event. Clinically, patients can exhibit dyspnea, tachypnea, cyanosis, dizziness, chest pain, cough, or hemoptysis; and eventually may lead to cardio-respiratory compromise [6,9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presentation can vary from an incidental radiological finding to a life-threatening event. Clinically, patients can exhibit dyspnea, tachypnea, cyanosis, dizziness, chest pain, cough, or hemoptysis; and eventually may lead to cardio-respiratory compromise [6,9].…”
Section: Discussionmentioning
confidence: 99%
“…A high index of clinical suspicion and imaging tools are crucial for the diagnosis of PCE. No screening methods have been implicated for asymptomatic patients, while some clinicians do recommend routine imaging after vertebral augmentation procedures [9,12]. A Chest X-ray revealing single or multiple high-density opacities in a tubular or branching pattern, matching to the pulmonary arterial distribution, is often indicative of PCE [2,3,9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported PCE as solitary or multiple, tubular or branching, radiodense lines in the lungs on chest radiographs [ 4 11 ]. Also suggestive of PCE on chest radiography are areas of high-density opacity in a tubular branching pattern that correspond to the distribution of arteries [ 26 29 ]. In a study in which chest CT scans were used to document the presence of PCE, the detected PCEs were also evident on plain radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…В отличие от классической легочной тромбоэмболии, полиметилметакрилат (костный цемент) обладает значительно более высокой плотностью по сравнению с плотностью паренхимы легкого, что позволяет без особого труда распознавать ЭЛА у больных, перенесших ЧКВП, при проведении обычной РГ ОГК [37]. Чаще всего подобные эмболические осложнения ЧКВП описываются в виде единичных или множественных линейных или «ветвящихся» теней, реже -как участки затенения легочной ткани высокой плотности в проекции предполагаемого деления ветвей легочной артерии [30,32,34,41]. В этом плане интересны результа ты исследования D.H.Choe et al [32], по результатам которых показано, что во всех случаях визуализации ЭЛА при ЧКВП при использовании КТ ОГК соответствующие фрагменты костного цемента удавалось распознать и при анализе обычной РГ ОГК.…”
Section: диагностика эмболии легочной артерии при чрескожной вертеброunclassified